The z-classes of quaternionic hyperbolic isometries - Gongopadhyay, Krishnendu (De Gruyter, 2013)
Let be the n-dimensional quaternionic hyperbolic space. The group acts as the isometry group of . We analyze when two isometries of commute. We apply this analysis to determine the conjugacy classes of centralizers or the z-classes in . Furthermore, we count the conjugacy classes of centralizers. In Appendix A, we show that our methods can be used to obtain the centralizers up to conjugacy in real and complex hyperbolic geometries as well. This provides a unified approach to the determination of the conjugacy classes of centralizers in hyperbolic geometries.
Keywords: Isometry group; n-dimensional; . The group acts as the; Quaternionic hyperbolic space